Pulmonary alveolar microlithiasis combined with gastric mucosal calcification: a case report - Li, Wen-Zhuo; Liu, Shuo; Luo, Ji-Li; Xia, Jing (Frontiers in Medicine, 2024)
Background Pulmonary alveolar microlithiasis (PAM) is a rare disease whose clinical and imaging manifestations are non-specific, characterized by the deposition of microliths, which primarily consist of calcium and phosphorus, within the alveoli. In the cases of PAM, patients combined with calcification of other organs such as gastric mucosal calcification are less common. Case presentation A 59-year-old woman was admitted to our hospital due to cough producing white, foamy sputum, accompanied by dyspnea and fever for 20 days. The CT scan showed diffuse ground-glass opacities and calcification of the gastric mucosa. Lung tissue biopsy revealed the presence of calcification and granulomatous foreign bodies in the interstitium and alveolar cavity. In the later stages, she developed painful skin petechiae. For this patient, the diagnosis of PAM, gastric mucosal calcification, and purpura fulminans was made. However, the genetic test results hinted that the patient and her son had a heterozygous mutation in the FBN1 gene, but her daughter's genetic test results were normal. Although the patient received anti-infection treatment, steroids, and oxygen therapy, her condition did not improve. Conclusion We reported a rare case of PAM combined with calcification of other organs and purpura fulminans. Treatment of steroids did not show any benefit. The causative mechanism and effective treatment of this disease remain unclear. More treatments need to be explored.